FAKTOR-FAKTOR YANG MEMPENGARUHI PROGRAM JAMINAN KESEHATAN MASYARAKAT DI KELURAHAN SUNGAI JAWI DALAM - Era Afna Purnata E.21111096 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Writing a journal is intended to find out the process of implementing a public health insurance program in urban rivers in the ox . The problem in this study are still some people who have not registered are less capable as a health plan members . This happens because the government Jawi In River village still lacks the human resources in the collection of the poor . The purpose of this study was to determine the factors that affect the implementation of the Community Health Insurance Program in Urban River in Jawi . The method used in this research is descriptive qualitative analysis . The results showed in the process of implementing a health program targeted at policy targets underprivileged citizens , but there are still some people who have not registered . River Village Office resource Jawi work is still needed to improve the facilities and employees who have competence in the field of public service . Communication between organizations in the implementation of a health program in urban rivers in the ox has been going pretty well between the villages , health centers / hospitals and health authorities . Social and economic conditions also influence the success of a health program , social and economic conditions of the river ox in fairly good already and support the process of program implementation JAMKESMAS . From these results it can be concluded that the implementation of the program in the Village of River JAMKESMAS Jawi In not running optimallyKeywords : policy implementation , health insurance , resources